Design of a Solar Dryer for Tomatoes. - Bwire, Samlex Sibagaya (Kabale University, 2025)
Natural solar drying is a practical method for removing moisture from agricultural products. However, various issues arise in such processes, such as bird, insect, or other animal attacks, fungal attacks, unexpected changes in weather, low or prolonged exposure to the sun, dust mixing, and so on. Electric dehydrators offer faster drying but rely on potentially unavailable or expensive electricity. This project addresses this gap by proposing the design, development, and testing of a solar dryer specifically for drying tomatoes. The solar dryer aims to reduce post-harvest tomato losses, improve drying efficiency, minimize contamination, and offer a cost-effective solution, particularly for small-scale producers and regions with limited resources. The project will involve, Determining the design parameters of a tomato solar dryer, Selecting and sizing components of a tomato solar dryer, and developing a solar dryer layout. The air allowed in through the air inlet is heated up in the solar collector and channeled through the drying chamber where it is utilized in drying. The design was based on the geographical location which is kabale and meteorological data were obtained for proper design specification. The optimum temperature of the dryer was 60 0C with a corresponding ambient temperature of 25 0C. The mass of water removal of 199.9g and 153.6g in cassava and plantain respectively using the solar dryer was achieved as against 156.8g and 125.3g in cassava and plantain respectively using the sun drying method and indicating 43.1g and 28.3g difference respectively, for ten slices of cassava and plantain dried over a particular day. The rapid rate of drying in the dryer reveals its ability to dry food items reasonably rapidly to safe moisture. The anticipated timeline is 3 months. The project budget will cover instrumentation for data collection during testing and potential travel for field testing. By developing a user-friendly and cost-effective solar dryer, this project has the potential to significantly reduce tomato post-harvest losses, improve food quality and safety, and empower small-scale producers, contributing to a more sustainable and secure food system.